2005
DOI: 10.1590/s0101-31222005000100004
|View full text |Cite
|
Sign up to set email alerts
|

Teste de condutividade elétrica para as sementes de pimentão

Abstract: RESUMO -A pesquisa teve como objetivo estabelecer metodologia para o teste de condutividade elétrica em sementes de pimentão envolvendo períodos de embebição da semente e temperaturas da água. Assim, utilizando cinco lotes de sementes de pimentão, cultivar Magali R, foram estudados os períodos de 1, 2, 3, 4, 5, 6 e 24 horas de embebição das sementes, 25 sementes em 25ml de água destilada, e as temperaturas de 25°C e de 30°C. Paralelamente, foram avaliados o teor de água das sementes, a germinação, a emergência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
2
4
1
7
Order By: Relevance
“…Em contrapartida, para as sementes de alface, de berinjela, de maxixe, de pimentão e de várias espécies do gênero Brassica (Guimarães et al, 1993;Torres, et al, 1998;Novembre, et al, 2002;Novembre, 2005;Hampton et al, 2009) o teste foi eficiente. Dessa forma, a eficiência do teste de condutividade elétrica para estimar o vigor de sementes depende da espécie vegetal que é avaliada.…”
Section: Resultsunclassified
“…Em contrapartida, para as sementes de alface, de berinjela, de maxixe, de pimentão e de várias espécies do gênero Brassica (Guimarães et al, 1993;Torres, et al, 1998;Novembre, et al, 2002;Novembre, 2005;Hampton et al, 2009) o teste foi eficiente. Dessa forma, a eficiência do teste de condutividade elétrica para estimar o vigor de sementes depende da espécie vegetal que é avaliada.…”
Section: Resultsunclassified
“…According to Araujo et al (2011), electrical conductivity test is used as a vigour test with promising results, mainly for peanut (Vanzolini and Nakagawa, 2005), cowpea and some vegetable crops like pumpkin (Vieira and Dutra, 2006) and pepper seeds (Oliveira and Novembre, 2005). For more studied crops such as cauliflower, radish, and turnip, immersion period of seeds in conductivity test can be reduced because the amount of released solute is very high as the imbibition starts and decreases as the reorganization system of membranes occurs.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…It has been shown that the imbibition period for the electrical conductivity test can be reduced from 24 h to 4-8 hours (Martins et al, 2002, with broccoli;Oliveira & Novembre, 2005, with pepper), the samples from 50 to 25 seeds and the water volume from 75 mL to 50 mL or 25 mL (Oliveira & Novembre, 2005). In addition, results of the potassium leachate test which is based on a principle similar to the electrical conductivity are obtained within a considerably shorter period of time, e.g., after 30 to 90 minutes of imbibition (Custódio & Marcos-Filho, 1997;Dias et al, 1998), but most of research has been performed on grain crops.…”
Section: Introductionmentioning
confidence: 99%